PENINGKATAN PRODUKSI TANAMAN JAGUNG PADA PERLAKUAN PUPUK NPK MUTIARA DALAM MENINGKATKAN PEREKONOMIAN PETANI DI KELURAHAN MALOTONG - Nuranisa Nuranisa; Muhammad Amiruddin; Diky Dwiyanto; Jusriadi Jusriadi; Sitti Aminah Karim (Jurnal Abdi Masyarakat Multidisiplin, 2022)
Corn is a food crop that is very much needed by humans because it is a source of carbohydrates after rice, besides that corn is also a much needed animal feed ingredient. The aim of the research was to examine the effect of growth and increase in yield of corn on the treatment of Pearl NPK Fertilizer. This study used an experimental design, namely a randomized block design (RAK), with a pattern of giving Pearl NPK Fertilizer which consisted of three levels, namely Without Pearl NPK Fertilizer (P1), One-time Fertilization (P2), Two-time Fertilization (P3), Three-time Fertilization (P4) . So that there were four treatments, each treatment was repeated three times so that there were 12 experimental units. The best fertilization results given are fertilization twice.